Evaluating the Potential of Marine Invertebrate and Insect Protein Hydrolysates to Reduce Fetal Bovine Serum in Cell Culture Media for Cultivated Fish Production - Inayat Batish; Mohammad Zarei; Nitin Nitin; Reza Ovissipour (Biomolecules, 2022)
The use of fetal bovine serum (FBS) and the price of cell culture media are the key constraints for developing serum-free cost-effective media. This study aims to replace or reduce the typical 10% serum application in fish cell culture media by applying protein hydrolysates from insects and marine invertebrate species for the growth of Zebrafish embryonic stem cells (ESC) as the model organism. Protein hydrolysates were produced from black soldier flies (BSF), crickets, oysters, mussels, and lugworms with a high protein content, suitable functional properties, and adequate amino-acid composition, with the degree of hydrolysis from 18.24 to 33.52%. Protein hydrolysates at low concentrations from 0.001 to 0.1 mg/mL in combination with 1 and 2.5% serums significantly increased cell growth compared to the control groups (5 and 10% serums) (p < 0.05). All protein hydrolysates with concentrations of 1 and 10 mg/mL were found to be toxic to cells and significantly reduced cell growth and performance (p < 0.05). However, except for crickets, all the hydrolysates were able to restore or significantly increase cell growth and viability with 50% less serum at concentrations of 0.001, 0.01, and 0.1 mg/mL. Although cell growth was enhanced at lower concentrations of protein hydrolysates, the cell morphology was altered due to the lack of serum. The lactate dehydrogenase (LDH) activity results indicated that BSF and lugworm hydrolysates did not alter the cell membrane. In addition, light and fluorescence imaging revealed that the cell morphological features were comparable to those of the 10% serum control group. Overall, lugworm and BSF hydrolysates reduced the serum by up to 90% while preserving excellent cell health.